6(2x+4)+4(x-1)=68

Simple and best practice solution for 6(2x+4)+4(x-1)=68 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x+4)+4(x-1)=68 equation:


Simplifying
6(2x + 4) + 4(x + -1) = 68

Reorder the terms:
6(4 + 2x) + 4(x + -1) = 68
(4 * 6 + 2x * 6) + 4(x + -1) = 68
(24 + 12x) + 4(x + -1) = 68

Reorder the terms:
24 + 12x + 4(-1 + x) = 68
24 + 12x + (-1 * 4 + x * 4) = 68
24 + 12x + (-4 + 4x) = 68

Reorder the terms:
24 + -4 + 12x + 4x = 68

Combine like terms: 24 + -4 = 20
20 + 12x + 4x = 68

Combine like terms: 12x + 4x = 16x
20 + 16x = 68

Solving
20 + 16x = 68

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + -20 + 16x = 68 + -20

Combine like terms: 20 + -20 = 0
0 + 16x = 68 + -20
16x = 68 + -20

Combine like terms: 68 + -20 = 48
16x = 48

Divide each side by '16'.
x = 3

Simplifying
x = 3

See similar equations:

| 4x+6=-16-7 | | 16x^2-40x+18=0 | | 0.5(x+100)+0.5x=75 | | 75-3x=33x+23 | | W^2+3=7w | | -(7y+1)-(6y-8)=7 | | a^2+6a=-3 | | 13-9x=106-30x | | 0.60x+.05(2-x)=.10(-98) | | -156-10=8x+24 | | 2(8s+5)-6s=2(5s+3)-7 | | 16x^2-19x+18=0 | | -2p+8=5-(7p+4) | | 3x+7=8x+13 | | 11x+=5x+37 | | 0.3(x+70)+1.5x=102 | | 3+p=9 | | -(3y+4)-(-2y-7)=-2 | | 144x^2-169y^2=0 | | 0.70x+.05(6-x)=.10(16) | | 8x^2+11xy+3y^2=0 | | x+12y+11x-13y-9= | | 8(x+5)=4(2x+3)+28 | | 4x-17=(3x-2)*4 | | 3x-3=7x+12 | | 4x=3y | | 3x-3=7x-12 | | 9x+5-4x-3+x=146 | | 2-6t-9-2t= | | -6-(2-3p)= | | -8n-9+7n= | | -[2z-(11z+1)]=1+(8z+6) |

Equations solver categories